Immune sensing of microbial glycolipids and related conjugates by T cells and the pattern recognition receptors MCL and Mincle. (February 2016) - Smith, Dylan G.M.; Williams, Spencer J.
Highlights: The innate immune system recognizes microbe-associated molecular patterns including glycolipids and vitamin-derived species. Pattern-recognition receptors including Mincle and MCL sense glycolipids from bacteria and fungi resulting in signalling and cellular activation. The CD1 group of antigen-presenting molecules presents lipid-like molecules to assorted T cell populations. The MR1 antigen-presenting molecule presents vitamin B metabolites to innate-like mucosal associated T cells. Graphical abstract: Abstract: Microbes produce a wide range of small molecule glycoconjugates that constitute unique molecular signatures. These molecules are recognized by a range of detection systems, triggering immune responses to microbial pathogens and commensals. The antigen-presenting molecules of the CD1 class, CD1a-d, capture lipidic molecules and present them to diverse and innate-like T cell populations including natural killer T cells and germline-encoded mycolyl reactive T cells. The antigen-presenting molecule MR1 captures vitamin B metabolites and presents them to mucosal associated invariant T cells. In both cases, recognition of the small molecule-antigen presenting molecule complexes occurs through T cell receptors on the surface of T lymphocytes. The pattern recognition receptors macrophage C-type lectin (MCL) and macrophage inducible C-type lectin (Mincle) receptors sense glycolipids and through signalling initiate cellular activation, shaping immune responses to peptide antigens, including the differentiation of naïve T cells into conventional effector T helper cells. In this review, we provide an overview of the diverse structures of immunogenic lipidic molecules and vitamin B metabolites and their recognition by select systems of the immune system. Future advances in our understanding of the roles of such molecules in innate and adaptive immune responses will require the coordinated efforts of synthetic and natural products chemists, immunologists and biologists.